Elevated expression of protease-activated receptor 1 via ΔNp63 down-regulation contributes to nodal metastasis in oral squamous cell carcinoma. Issue 2 (February 2021) - Hattori, T.; Kawano, S.; Tanaka, S.; Matsubara, R.; Sakamoto, T.; Hashiguchi, Y.; Kaneko, N.; Mikami, Y.; Morioka, M.; Maruse, Y.; Kitamura, R.; Hamada, E.; et al.
Abstract: Protease-activated receptor 1 (PAR1) is known as a thrombin receptor. Recent studies have reported PAR1 expression in various malignancies; however, its role in oral squamous cell carcinoma (OSCC) requires clarification. A previous study showed that down-regulation of ΔNp63, a homolog of p53, augments PAR1 expression in OSCC. In the present study, the association of PAR1 expression with clinicopathological findings in OSCC was examined retrospectively. Expression of PAR1, thrombin, and ΔNp63 was examined immunohistochemically in OSCC specimens. Patients were divided into three groups based on the expression pattern of PAR1 at the invasive front: group A, PAR1-negative in both cancer and stromal cells; group B, positive in stromal cells but negative in cancer cells; group C, positive in both cancer and stromal cells. Histologically high-grade tumours were significantly more common in group C. Patients in group C had the highest incidence rate of nodal metastasis ( P < 0.001) and a lower survival rate ( P = 0.085) than those in the other groups. At the invasive front, in group C, thrombin was expressed but ΔNp63 expression was weak. These results indicate that increased PAR1 expression in both cancer and stromal cells could be a useful predictive marker of nodal metastasis and that ΔNp63 is involved in regulating PAR1 expression.